REVITALISASI INDONESIA INCORPORATED: SUPER HOLDING DAN INTERNASIONALISASI BUMN INDONESIA - Triarda, Reza; Zulfikar, Rafli (Jurnal Transformasi Global, 2019)
State-owned enterprises (SOEs) ought to taking responsibility to serve public needs of a country. But along with the globalization, the world also exposed the government encourages their enterprises to invest overseas and compete in the global market. To coping with globalization and prevent economical slowdown Indonesia’s Government encouraging SOEs with a mechanism called Indonesia Incorporated. Indonesia Inc. is not a new concept for Indonesia, this concept was adopted from Japan Inc., but in early implementation was failed. Now, Kementerian BUMN Indonesia (Ministry of Indonesian SOEs) initiate to revitalize Indonesian Inc. with established super holding SOEs mechanism. Therefore, this article is trying to shows how revitalization mechanism happen, and find whether this concept still relevance or not. Finally, this article aiming to shows that holding mechanism and Indonesian Inc. will contribute significance to SOEs management and for Indonesian economic development.Keywords: Revitalization, super holding, Indonesian incorporated, State-owned Enterprises, Internationalization,